Pengaruh Shopping Lifestyle, Online Customer Review dan Price Discount terhadap Impulse Buying (Studi pada Pengguna Tiktok di Kota Medan) - Conita, Tiara; Mardhiyah, Ainun (Jurnal Disrupsi Bisnis, 2024)
Internet technology is currently experiencing rapid development. The human need to access something can now be made easier through internet-based information searches. This situation is in accordance with the human desire to obtain information quickly and easily. With the internet, many people now switch shopping from offline to online. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out through non-probability sampling with purposive sampling technique with 100 respondents as samples. Primary data used in this research was obtained by distributing questionnaires directly, while secondary data was obtained through literature study. The data analysis methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression testing, and hypothesis testing. The results of the research conducted show that the variables shopping lifestyle (X1), online customer reviews (X2) and price discounts (X3) have a significant effect on impulse buying (Y) and all independent variables simultaneously (simultaneously) influence impulse buying (Y).